Let's get physical: Biomechanical influences on human pluripotent stem cell differentiation towards vascular engineering. (March 2018) - Chan, Xin Yi; Eoh, Joon H.; Gerecht, Sharon
Abstract: Regenerative medicine provides a promising avenue of research in which tissue lost from disease, trauma and congenital defects can be replaced from substitutes created in the laboratory. Human pluripotent stem cells (hPSCs) are of great interest in the field of cell therapy due to their ability to provide a patient-specific cell source for the supplementation of tissue engineering constructs. In the field of vascular tissue engineering, blood vessels are composite tissues comprised of various cell types, mainly endothelial cells and smooth muscle cells. Therefore, proper attention must be given to the differentiation process so that the appropriate cell type with the necessary functional properties can be obtained. A larger emphasis needs to be placed on optimizing the functional properties of these cells so that they can withstand physiologically relevant forces in the native environment and integrate into the patients' vasculature. Despite the importance of biomechanical cues in vascular development and engineering, few studies have investigated these critical factors during the differentiation of hPSCs into functional vascular cells and tissue. In this review, we summarize recent findings that elucidate the role of biomechanical influences on the differentiation of hPSCs. Specifically, we focus on their role in the differentiation of hPSCs into endothelial cells and smooth muscle cells. It is now evident that the use of these factors during differentiation can not only better direct cell fate, but can in fact enhance the specification and functionality of the differentiated cells. Finally, future directions and additional considerations for the use of biomechanical cues in the field of vascular bioengineering will be discussed. Graphical abstract: This schematic displays various biophysical cues that can be used during the differentiation of human pluripotent stem cells to yield specific vascular cell types. The goal is that these biomechanical cues used during differentiation will result in cells with the functional characteristics necessary for withstanding the physiological environment. This will then allow us to engineer complex tissues tailored for patient-specific therapies.